2022
DOI: 10.1063/5.0081874
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration and modeling of time-bin entangled photons from a quantum dot in a nanowire

Abstract: Resonant excitation of the biexciton state in an InAsP quantum dot by a phase-coherent pair of picosecond pulses allows preparing time-bin entangled pairs of photons via the biexciton–exciton cascade. We show that this scheme can be implemented for a dot embedded in an InP nanowire. The underlying physical mechanisms can be represented and quantitatively analyzed by an effective three-level open system master equation. Simulation parameters including decay and intensity dependent dephasing rates are extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In 2017, Jöns K. D. et al used self-organized grown nanowires collected ~200 kHz entangled photon pairs at the first lens under 80 MHz pulsed excitation, which was a 20 times enhancement as compared to a bare quantum dot without a photonic nanostructure, and the entanglement fidelity was 81.7% ± 0.2% [91]. In 2022, Aumann P et al have shown the coherent coupling of the ground to biexciton state of an InAsP QD embedded in an InP nanowire via an optimized two-photon resonant excitation scheme and generated time-bin entangled photons, yielding a fidelity of 90% with respect to the maximally entangled Bell state [92]. Microlenses are another commonly used structure for extracting entangled photon pairs.…”
Section: Artificial Microstructures Enhanced Entangled Photon Emissio...mentioning
confidence: 99%
“…In 2017, Jöns K. D. et al used self-organized grown nanowires collected ~200 kHz entangled photon pairs at the first lens under 80 MHz pulsed excitation, which was a 20 times enhancement as compared to a bare quantum dot without a photonic nanostructure, and the entanglement fidelity was 81.7% ± 0.2% [91]. In 2022, Aumann P et al have shown the coherent coupling of the ground to biexciton state of an InAsP QD embedded in an InP nanowire via an optimized two-photon resonant excitation scheme and generated time-bin entangled photons, yielding a fidelity of 90% with respect to the maximally entangled Bell state [92]. Microlenses are another commonly used structure for extracting entangled photon pairs.…”
Section: Artificial Microstructures Enhanced Entangled Photon Emissio...mentioning
confidence: 99%
“…Exciting the biexciton state is of particular interest since it can generate entangled photon pairs for various encoding schemes, e.g. polarization or time-bin [8,51,52], in addition to offering a simple method to generate multiplexed single photons, towards advanced quantum communication protocols. Our results pave the way for practical realization of spatio-spectrally multiplexed single photons and entangled photon pairs from the same source.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum entanglement [1] is important because it plays a key role in a range of quantum devices, notably in induced coherence [2][3][4] based quantum imaging/QNI schemes [5][6][7][8][9][10][11][12]; and in the time domain is a subject of wide-ranging and active study [13][14][15][16][17]. However, the complicating effects of material dispersion in the entanglement-generating nonlinear medium, or during subsequent propagation, are typically not considered [18][19][20].…”
Section: Introductionmentioning
confidence: 99%